2014
DOI: 10.3346/jkms.2014.29.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Effect of Erythropoietin Injection to Prevent Acute Mountain Sickness: An Open-Label Randomized Controlled Trial

Abstract: This study was performed to evaluate whether increasing hemoglobin before ascent by prophylactic erythropoietin injections prevents acute mountain sickness (AMS). This open-label, randomized, controlled trial involved 39 healthy volunteers with hemoglobin ≤15.5 g/dL who were divided randomly into erythropoietin (n=20) and control (n=19) groups. Epoetin alpha 10,000 IU injections were given weekly for four consecutive weeks. On day 1, and 7 days after the last injection (day 29), oxygen saturation (SaO2), and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…peripheral chemosensitivity, in humans as likewise seen before in mice (Soliz et al 2009). Only marginally related, acute mountain sickness, characterized by headache, gastrointestinal symptoms, weakness, dizziness or lightheadedness, and difficulty sleeping in an unacclimatized person who recently arrived at an altitude above 2500 m, was prevented by prophylactic EPO injections (Heo et al 2014). Efficacy of EPO versus placebo in critically ill patients, including those with lung disease admitted to intensive care, yielded reduction in allogeneic red blood cell transfusion.…”
Section: Introductionmentioning
confidence: 69%
“…peripheral chemosensitivity, in humans as likewise seen before in mice (Soliz et al 2009). Only marginally related, acute mountain sickness, characterized by headache, gastrointestinal symptoms, weakness, dizziness or lightheadedness, and difficulty sleeping in an unacclimatized person who recently arrived at an altitude above 2500 m, was prevented by prophylactic EPO injections (Heo et al 2014). Efficacy of EPO versus placebo in critically ill patients, including those with lung disease admitted to intensive care, yielded reduction in allogeneic red blood cell transfusion.…”
Section: Introductionmentioning
confidence: 69%
“…Interestingly, hypoxia stress can stimulate the production of reticulocytes (MacNutt et al, 2013 ), and young mature RBCs have greater affinity for oxygen plus more efficient oxygen delivery to the tissues, compared to old RBCs (Samaja et al, 1991 ; Cohen and Matot, 2013 ). Moreover, a recent open-label randomized controlled trial revealed that erythropoietin (which stimulates hematopoiesis) is an effective prophylaxis for AMS (Heo et al, 2014 ). Therefore, our results may support the prevention of HAH using prophylactic induction of hematopoiesis in case with anticipated acute exposure to a hypoxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these postulated mechanisms of action have never been shown in humans and the transferability of these findings to the clinical situation of a hypoxemic COVID-19 patient is questionable at best. In support of their suggestion they cite on an open-labeled trial reporting that four injections of erythropoietin preceding acute exposure to 4130 m reduced severity and incidence of AMS (Heo et al, 2014). It is noteworthy that sildenafil was given in this study twice daily >2360 m for prevention of HAPE.…”
Section: Role Of Angiotensin Converting Enzymementioning
confidence: 57%